ISO Surveys of a Dusty Universe: Proceedings of a Ringberg Workshop Held at Ringberg Castle, Tegernsee, Germany, 8–12 November 1999 - Lemke, Dietrich (Lecture notes in physics, 2000)
The unprecedented sensitivity of the Infrared Space Observatory and the far-infrared window provided by IRAS led to spectroscopic surveys throughout the entire infrared region. In particular, the high resolution allowed for pointed observations of individual sources. The authors of this volume are principal investigators of the ISO mission and present a host of new data analyses that should trigger novel astrophysical research in the far-infrared. A particular feature of the book is the emphasis on object-oriented presentation of the observations. The book addresses researchers and students alike
Keywords: Konferenzschrift -- 1999 -- Ringberg, Tegernsee; ISO